METHODOLOGICAL ASPECTS OF REPORTING OF ENTERPRISES IN WARTIME - Yuliia Remyha; Nataliya Pryimak (Izdevnieciba "Baltija Publishing", 2022)
The purpose of the article is to determine the peculiarities and correctness of preparation and submission of reporting information by business entities in difficult conditions, namely during martial law in Ukraine. Methodology. The methodological basis of the study is the theory of cognition, a systematic approach to the study and improvement of the organization and methodology of management reporting by business entities under martial law in Ukraine to meet the information needs of stakeholders. The methods of generalization, comparison, analysis, synthesis, induction and deduction were used in the process of substantiating the rules for the formation and submission of management reporting, as well as the reflection of risks in the use of credit resources by business entities in the conditions of war in Ukraine. Results. The scientific article reveals the peculiarities of management reporting under martial law, in particular: the importance of creating a management report at the legislative level is revealed; a fragment of the management report on the direction "Liquidity and liabilities", namely in terms of long-term and current credit resources, is proposed; a fragment of the management report in the section "Risks" is presented; the methodology for filling in information about risks is outlined. Practical implications. Despite the state of war, the timely submission of information on the financial condition and performance of various business entities remains an important and timely topic. This makes it possible to timely respond to problematic aspects of market participants' activities by amending legislation and regulations. The proposed fragments of the Management Report, as well as the algorithm for filling in the relevant indicators of Section 6 "Risks" of the Management Report, make it possible to develop information support for the management of such risks at enterprises in general. Value/originality. The value of the study is the fragments of reporting documents proposed by the authors, namely the management report, the management report in the section "Risks", as well as algorithms for filling them out.